Analisis Contract Change Order Terhadap Waktu pada Proyek Pembangunan Stasiun Kereta Api Makassar-Pare pare - Milenia Inri S. Mangampa; Josefine E Latupeirissa; Herby Calvin P Tiyouw (Paulus Civil Engineering Journal, 2022)
Contract Change Order (CCO) is a change to the initial contract value that commonly occurs in construction work. This study is intended to determine the causal factors and analyze the impact of the Contract Change Order (CCO) on the Makassar-Pare Pare Railway Station construction project. The method in this research is to use the SPSS method and the Relative Rank Index (RRI) method to determine the causal factors and the mean value method to analyze the impact of the Contract Change Order (CCO) on the construction of the Makassar-Pare Pare Railway Station. The results showed that there were 5 dominant factors that caused the Contract Change Order (CCO) to occur, namely the difficulty of land acquisition by the community, the demand factor from the project owner (owner) to change the initial design, place characteristics factors, physical condition factors in the field that are different from the initial conditions. time for field inspections, and force majeure factors such as the Covid-19 Pandemic and the impact it causes is an extension of the implementation time, an extension of time for the duration of work, and an increase in Overhead costs.